Temperature sensitivity of fibre bragg gratings fabricated in high Germania boron co-doped optical fibre - Harun, S.W.; P. Poopalan; Ahmad, H. (Universiti Kebangsaan Malaysia, 2002)
The Bragg wavelength drift in fibre Bragg gratings (FBGS) fabricated in high germania boron co-doped optical fibre with respect to temperature variation is studied. The FBG is subjected to temperature variation using an oven. The Bragg wavelength shift with temperature variation is mostly due to thermooptic effects. The main constituent of the FBG fibre is silica and germanosilicate glass for which the wavelength increases with temperature. The experimental result shows that the thermal response for the FBG is about 0.010 nmoC, which is consistent with theoretical prediction.